Context matters: adapting and validating the TEDS-instruct observation instrument assessing teaching quality for its use in Norwegian primary education - Senden, Bas; Jentsch, Armin; Teig, Nani; Nilsen, Trude; Fauskanger, Janne; Frågåt, Thomas; Maugesten, Marianne; Mork, Sonja Merethe; Mosvold, Reidar; Nortvedt, Guri A.; Olufsen, Magne; Sjøberg, Mari; et al. (Frontiers in Education, 2025)
The current investigation aims to adapt and validate the Teacher Education and Development Study-Instruct observation instrument for assessing teaching quality in new contexts: Norwegian Grade 6 mathematics and science lessons. More specifically, the article examines content validity and reliability in the new contexts using a multi-methods approach, involving the Delphi technique and generalizability theory. Findings suggest that while the core components of the instrument are relevant in the new contexts, specific adaptations are necessary to capture teaching quality in a more nuanced and meaningful way. Based on the findings, specific adaptions are made to the instrument. Finally, recommendations for developing and using the instrument in the new contexts are provided. The current investigation underscores the importance of contextual sensitivity in the assessment of teaching quality.